Inflammatory Immune Responses Trigger Rejection of Allogeneic Fibroblasts Transplanted into Mouse Skin. (July 2022) - Farrokhi, Ali; Rahavi, MohammadReza; Jo, Sumin; Jalili, Reza; Lim, C. James; Ghahsary, Aziz; Reid, Gregor S. D.
Fibroblasts, or their homolog stromal cells, are present in most tissues and play an essential role in tissue homeostasis and regeneration. As a result, fibroblast-based strategies have been widely employed in tissue engineering. However, while considered to have immunosuppressive properties, the survival and functionality of allogeneic fibroblasts after transplantation remain controversial. Here, we evaluated innate and adaptive immune responses against allogeneic fibroblasts following intradermal injection into different immune-deficient mouse strains. While allogeneic fibroblasts were rejected 1 week after transplantation in immunocompetent mice, rejection did not occur in immunodeficient γ chain–deficient NOD-SCID (NSG) mice. T-cell- and B-cell-deficient RAG1 knockout mice showed greater loss of fibroblasts by day 5 after transplantation compared with NSG mice ( P ≤ 0.05) but prolonged persistence compared with wild-type recipient ( P ≤ 0.005). Loss of fibroblasts correlated with the expression of proinflammatory chemokine genes and infiltration of myeloid cells in the transplantation site. Depletion of macrophages and neutrophils delayed rejection, revealing the role of innate immune cells in an early elimination of fibroblasts that is followed by T-cell-mediated rejection in the second week. These findings indicate that the application of allogeneic fibroblasts in tissue engineering products requires further improvements to overcome cell rejection by innate and adaptive immune cells.